Educational priorities and programs for the development of research competencies in science-based medical education - Ch. S. Pavlov; V. I. Kovalevskaya; N. V. Kireeva; E. N. Dudnik; E. I. Voronova; T. M. Litvinova; B. A. Volel (Кардиоваскулярная терапия и профилактика)
The active development of technology since the middle of the 20th century has changed the requirements for education in view of the demand for knowledge-intensive specialties. The current approach is focused on the intersubjectivity and complexity of problem solving, the project organization of training and the practical orientation of learning courses. The training of specialists capable of solving qualitatively new tasks is possible only in a special environment where personal and professional competencies are formed. The transformation of education in medicine has led to the active integration of research and clinical experience. A significant impetus for the transition to a new level is provided by the development of cognitive competencies, critical thinking, which is closely interrelated with evidence-based medicine. Novel training programs make it possible to receive research, management, entrepreneurial and communication competencies inaddition to classical clinical education. At present, the future belongs to interdisciplinary teams based on developed clusters.